2009
DOI: 10.1002/app.30897
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the molecular weight of poly(ether imide) on the viscoelastic phase separation of poly(ether imide)/epoxy blends

Abstract: ABSTRACT:The phase separation of diglycidyl ether of bisphenol A/methyl tetrahydrophthalic anhydride blends modified with three poly(ether imide)s (PEIs) of different molecular weights was investigated with scanning electron microscopy (SEM) and time-resolved light scattering (TRLS). The morphologies observed by SEM for the three blends were all close to a cocontinuous structure with different periodic distances. The results of TRLS indicated that the phase separation for the PEI-modified epoxy blends took pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 30 publications
3
20
0
Order By: Relevance
“…It was found that less PEI‐1w was needed to get bi‐continuous phase or phase‐inversion structure compared with PEI‐5K, which agreed well with elsewhere …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…It was found that less PEI‐1w was needed to get bi‐continuous phase or phase‐inversion structure compared with PEI‐5K, which agreed well with elsewhere …”
Section: Resultssupporting
confidence: 86%
“…Compared with rubbery materials, it has been reported that engineering thermoplastics improves the toughness of epoxy resin without decreasing most of the other mechanical properties and thermal stability. As a result, engineering thermoplastics, such as polyethersulfone (PES), polysulfone (PSF), poly(ether ether ketone), and polyetherimide (PEI), have been used as toughening agents of epoxy resin or other thermosetting resins.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the thickness of PEI/CB continuous phase is small and mostly not more than 5 mm by estimation from Figure 1(c), and it is worth noting that there are some smaller EP globules with a size of 2-3mm involved in PEI phase (in the lower left part of Figure 1(c)), which was also reported in the literature. 42 These smaller EP globules definitely affect the percolation behavior in EP/PEI/CB blends, and this behavior needs further investigation. From another point of view, as is shown in Figure 2, the morphology of EP84PEI16 and EP83PEI16CB1 blends was further observed using optical microscopy in a transmission mode.…”
Section: Microstructure Of Ep/pei/cb Compositesmentioning
confidence: 99%
“…However, most of the available studies compared the phase separation kinetics of blends with different molecular weights at the same temperature with the overlooking of the effect of quench depth [20,22,27,29,30].…”
Section: Introductionmentioning
confidence: 98%